Voluntourism: A Pathway to Sustainable Development or a Hidden Pitfall? - Gegung, Eunike; Panggabean, Marisi (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
Voluntourism is the extension of responsible tourism or alternative tourism. Voluntourism is further reinforced by a belief that tourism allows community empowerment. It may revive and maintain the welfare of local communities through eco-travel experiences. Visitors may not compromise with undesirable attitudes, but serve as goodwill ambassadors and express their compassion towards local communities and the ecosystem of the destination attraction. However, is it true that this practice is as green as it is touted? This research aims to analyze the implications of voluntourism and focus on an array of triple-bottom-line concepts of sustainability, namely, economic development, socio-cultural inclusion, and environmental impact, and the scope of the practical standard of these ecotravel practices. This study adopts a library-based research methodology, with data examined through a descriptive qualitative approach to provide comprehensive and contextually grounded insights. This approach used constant comparative analysis when examining the data to meet the purpose of the study. The result showed there are multiple gaps in implementing volunteer tourism in practice. However, as there is no single significance of this concept, there are several alternative solutions that can be implemented. VTO's role could be one ultimate factor in increasing the effectiveness of volunteer tourism best practice in the area visited. Furthermore, fostering projects that may allow a process of co-creation and co-presence among locals, tourists, and volunteer tourism organizations, and a need to look at how volunteer tourism is perceived by locals through the involvement of locals in the decision-making process on how VT projects may impact their areas.